2023
DOI: 10.1155/2023/1696190
|View full text |Cite
|
Sign up to set email alerts
|

P16INK4a Regulates ROS-Related Autophagy and CDK4/6-Mediated Proliferation: A New Target of Myocardial Regeneration Therapy

Abstract: Neonatal mice achieve complete cardiac repair through endogenous myocardial regeneration after apical resection (AR), but this capacity is rapidly lost 7 days after birth. As an upstream inhibitor of cyclin-dependent kinase 4/6- (CDK4/6-) mediated cell cycle activity, p16INK4a is widely involved in regulating tumor and senescence. Given that p16INK4a had a significant negative regulation on cell proliferation, targeting cardiomyocytes (CMs) to inhibit p16INK4a seems to be a promising attempt at myocardial rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In contrast, several studies have aimed to promote cardiomyocyte re-entry into the cell cycle by inhibiting CKIs. One study found that p16 knockdown extends the regeneration period in neonatal mice through CDK4/6 and reactive oxygen species (ROS)-related autophagy [ 167 ]. Another study demonstrated that specifically inactivating p16 in cardiomyocytes improves heart function and reduces scar size after a myocardial infarction [ 148 ].…”
Section: Manipulation Of the Cell Cycle To Induce Cardiomyocyte Proli...mentioning
confidence: 99%
“…In contrast, several studies have aimed to promote cardiomyocyte re-entry into the cell cycle by inhibiting CKIs. One study found that p16 knockdown extends the regeneration period in neonatal mice through CDK4/6 and reactive oxygen species (ROS)-related autophagy [ 167 ]. Another study demonstrated that specifically inactivating p16 in cardiomyocytes improves heart function and reduces scar size after a myocardial infarction [ 148 ].…”
Section: Manipulation Of the Cell Cycle To Induce Cardiomyocyte Proli...mentioning
confidence: 99%